THE STRUGGLE BETWEEN ROMANCE AND FAITH: STUDY OF THE DA'WAH MESSAGE IN THE MOVIE "AJARI AKU ISLAM" - Arni Ernawati (Profetik: Jurnal Komunikasi, 2022)
The form of Islamic da'wah is currently very rapidly advancing, as is the use of its da'wah media. Da'wah symbols are made more interesting for everyone. In the past, da’wah was delivered through events such as recitation or other formal educational events. One form of media used for da’wah is through film work. In 2019 the national film industry was enlivened by films with islamic themes. A film called “Ajari Aku Islam” carrying the theme of love wrapped in islamic background. In addition to being a means of entertainment, this film also contains messages of da’wah. By packaging da'wah in films, it is hoped that it can be a solution to improve the religious community. Combining pop themes or those currently favored by the community is also very useful for making films containing da'wah that can attract the attention of the audience. Attractive da'wah packaging is very much needed by today's people who really prioritize taste. The researcher uses a descriptive qualitative approach to reveal the message in the film that has been reviewed with semiotic theory. This paper found that maintaining faith is very important for Muslims and places faith above all else.The film combines Islamic da'wah wrapped in a romance story of teenagers of different religions. There was a very important da'wah message, one of them is as Muslims we must always maintain our faith until we die. Maintaining faith and Islam is very important for Muslims to do in any condition.